Increased red cell turnover in a line of CD22-deficient mice is caused by Gpi1c: A model for hereditary haemolytic anaemia - Walker, Jennifer A.; Hall, Andrew M.; Kotsopoulou, Ekaterini; Espeli, Marion; Nitschke, Lars; Barker, Robert N.; Lyons, Paul A.; Smith, Kenneth G. C. (European Journal of Immunology, 2012)
CD22, an inhibitory co-receptor of the BCR, has been identified as a potential candidate gene for the development of autoimmune haemolytic anaemia in mice. In this study, we have examined Cd22tm1Msn CD22-deficient mice and identified an increase in RBC turnover and stress erythropoiesis, which might be consistent with haemolysis. We then, however, eliminated CD22 deficiency as the cause of accelerated RBC turnover and established that enhanced RBC turnover occurs independently of B cells and anti-RBC autoanti-bodies. Accelerated RBC turnover in this particular strain of CD22-deficient mice is red cell intrinsic and appears to be the consequence of a defective allele of glucose phosphate isomerase, Gpi1c. This form of Gpi1 was originally derived from wild mice and results in a substantial reduction in enzyme activity. We have identified the polymorphism that causes impaired catalytic activity in the Gpi1c allele, and biochemically confirmed an approximate 75% reduction of GPI1 activity in Cd22-/- RBCs. The Cd22-/-.Gpi1c congenic mouse provides a novel animal model of GPI1-deficiency, which is one of the most common causes of chronic non-spherocytic haemolytic anaemia in humans.
Keywords: Anaemia; CD22; Erythrocytes; Glucose-6-phosphate isomerase; Polymorphism